2018
DOI: 10.5539/elt.v11n8p103
|View full text |Cite
|
Sign up to set email alerts
|

Arabic Learners’ Preferences for Instagram English Lessons

Abstract: This paper focuses on the use of the social network Instagram to provide supplementary English language learning material to learners from Arabic speaking countries. The author was able to use his online account in Instagram to assess the needs of these learners through data analyses. The content made specific to Arabic speakers by offering translation in each post from English into Arabic and vice versa to foster their interest in the English language. The account was followed by more than 48000 learners. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 17 publications
1
19
0
1
Order By: Relevance
“…Learners readily connect to vocabulary terms and meanings in English to those existing in their language than they do grammar conventions. Learners also expressed a desire for more AlGhamdi, 2018). This suggests that Instagram may be limited in the amount of information that can be effectively presented to the learner at a given moment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Learners readily connect to vocabulary terms and meanings in English to those existing in their language than they do grammar conventions. Learners also expressed a desire for more AlGhamdi, 2018). This suggests that Instagram may be limited in the amount of information that can be effectively presented to the learner at a given moment.…”
Section: Discussionmentioning
confidence: 99%
“…English language learners may prefer to use Instagram as a vehicle for lessons with a simple rather than complex structure. Alghamdi (2018) reported that Instagram lessons with a simple lesson structure received more views, likes, and comments than those with complex ones. Figure 1 illustrates these differences.…”
Section: Preferences In Using Instagram To Learning Englishmentioning
confidence: 99%
“…Trifiro (2018) revealed that Instagram use has the potential to enhance the users’ well-being and self-esteem. While there is a paucity of literature on Instagram use, few of the current studies revealed its potential for learning process (AlGhamdi, 2018; Gonulal, 2019). Lup et al.…”
Section: Introductionmentioning
confidence: 82%
“…As the influence of Instagram has been growing, it has begun to attract the attention of educational researchers, especially in higher education (AlGhamdi, 2018; Çakmak, 2019; Shafer et al., 2018). A variety of studies have found that fewer youngsters use social media platforms such as Facebook and Instagram for educational or academic purposes, and most of the youngsters prefer to use them for socializing and communication (Prescott et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Quanto aos objetivos, a presente investigação pode ser classificada como pesquisa exploratória, pois visa analisar os usos pedagógicos de uma rede social originalmente projetada para outro fim, o que possibilita a identificação de novas lacunas para futuras pesquisas e também corrobora os estudos publicados sobre o uso do Instagram como ferramenta educacional (AlGhamdi, 2018;Sari & Wahyudin, 2019;Davies, Lorne, & Sealey-Huggins, 2019 Instagram as quais possibilitam a interação entre os usuários e a produção de diversos tipos de conteúdo, inclusive educacionais.…”
Section: Metodologiaunclassified